2018
DOI: 10.1007/s00167-018-5178-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography has high positive predictive value for medial epicondyle lesions among adolescent baseball players

Abstract: Purpose Only few studies have investigated medial epicondyle (MEC) lesions, particularly in the 12-18 age group. To the best of our knowledge, no study has compared ultrasonography (US), radiography and magnetic resonance imaging (MRI) in detecting MEC lesions. The aims of this study were to examine the value of US for detecting MEC lesions and to investigate correlations among diagnostic tools. Methods A prospective, comparative study was performed. Young baseball players from southern Taiwan were recruited, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Stress imaging using radiography is performed as one of the examinations for valgus instability, and the same method using ultrasonography, which is a useful and less-invasive technique, has been used recently. 10 , 18 , 30 , 32 The validity and reliability of stress imaging using ultrasonography are slightly similar to those of stress imaging using radiography. Lee et al showed that the ulnohumeral distance of the uninjured elbow was 4.0 ± 0.7 mm and 4.7 ± 0.6 mm in the unloaded (gravity only) and loaded conditions (5 lb), respectively, using stress radiographs.…”
mentioning
confidence: 74%
“…Stress imaging using radiography is performed as one of the examinations for valgus instability, and the same method using ultrasonography, which is a useful and less-invasive technique, has been used recently. 10 , 18 , 30 , 32 The validity and reliability of stress imaging using ultrasonography are slightly similar to those of stress imaging using radiography. Lee et al showed that the ulnohumeral distance of the uninjured elbow was 4.0 ± 0.7 mm and 4.7 ± 0.6 mm in the unloaded (gravity only) and loaded conditions (5 lb), respectively, using stress radiographs.…”
mentioning
confidence: 74%
“… 33 , 34 Changes to the medial epicondyle of the throwing side also have been identified from youth to adolescent baseball players through the use of ultrasonography, radiography, or MRI. 23 , 26 , 28 , 37 Therefore, it is possible that similar adaptive changes may exist in the elbows of throwing athletes caused by the effects of repetitive throwing on the ulnar sublime tubercle. As a result, our modified technique could be an efficient surgical option in patients who have a small medial epicondyle.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Lee et al showed US efficacy in the diagnosis of medial epicondyle lesions as compared with RA and MRI, with US providing a good PPV of medial epicondyle lesions. 20 Through systematic literature review, Katzer et al concluded that there are hints of a comparable diagnostic accuracy of RA and US-based diagnosis of forearm fractures in children, in addition to being less painful, time saving, and cost-effective. 18 Comparing these pediatric applications with others as well as our results, the use of US for diagnosis in the pediatric sports patient appears promising.…”
Section: Discussionmentioning
confidence: 99%